2017
DOI: 10.1002/slct.201700420
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Carbon Cloth as Current Collector for Enhanced Electrochemical Performance of Lithium‐Rich Layered Oxide Cathodes

Abstract: In this study, pristine and modified carbon cloth replaced with Al foil as current collector for lithium‐rich layered oxide cathodes (Li1.2Mn0.6Ni0.2O2, LLO). The modified carbon cloths were prepared by modification of the pristine carbon cloth with phenolic resin (PR) and carbon nanotubes (CNT), followed by carbonization at 1000oC in nitrogen atmosphere. The first charge‐discharge capacities of the lithium‐rich layered oxide cathodes using the carbon cloth as current collector were 312 mAhg−1 and 252 mAhg−1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 76 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…Wang et al investigated the lithium-rich layered oxide cathode with carbon cloth as the current collector, which has achieved good rate performance (Figure 18b). [235] Gu et al reported that commercial CC could be activated simply by heating in air at a moderate temperature. [239] Pristine CC is not an attractive electrochemically active material due to its low areal specific capacitance arising from the poor electrochemical activity and small surface area.…”
Section: ) Bindersmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al investigated the lithium-rich layered oxide cathode with carbon cloth as the current collector, which has achieved good rate performance (Figure 18b). [235] Gu et al reported that commercial CC could be activated simply by heating in air at a moderate temperature. [239] Pristine CC is not an attractive electrochemically active material due to its low areal specific capacitance arising from the poor electrochemical activity and small surface area.…”
Section: ) Bindersmentioning
confidence: 99%
“…investigated the lithium‐rich layered oxide cathode with carbon cloth as the current collector, which has achieved good rate performance (Figure 18b). [ 235 ] Gu et al. reported that commercial CC could be activated simply by heating in air at a moderate temperature.…”
Section: High Mass‐loading Bpc Electrodesmentioning
confidence: 99%
“…Current collectors can greatly influence the performance of LIBs. For example, improving the electrical conductivity, reducing contact resistance and increasing the corrosion resistance of current collectors are beneficial to increase the capacity, rate capability, efficiency and cycle stability of LIBs [15]. Considering current collectors are essentially non-active materials in LIBs, reducing the thickness of current collectors can reduce the weight percentage and thus increase the energy density of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ]. For example, the improvement of conductivity and corrosion resistance of the current collector contributes to the improvement of capacity, charge and discharge efficiency, and cycle stability of LIBs [ 12 ]. Aluminum alloys are widely employed as current collectors in LIBs due to their excellent conductive properties.…”
Section: Introductionmentioning
confidence: 99%